Exploring the Plausibility of Pre-Purchase Decision Process in User Acceptance of Smart Wearable Technology Devices - Gupta, Prateek; Barkathunissa (Indian Journal of Marketing, 2021)
The market for smart wearable technology products is growing rapidly. Although wearable technology is still in its early stages, a longer-term outlook is required. This study inspected the existence of consumers’ pre-purchase stage for smart wearable technology devices. It further analyzed the factors that influenced customers’ decisions in the pre-purchase phase. The methodology adopted was quantitative, using which 240 users of smart wearables were given a structured questionnaire to fill up. The Smart PLS 3.0 software was used for structural equation modeling and path analysis. The results indicated that customers go through a pre-purchase decision journey. Their decisions are influenced by individual characteristics, product description, information source utility, data usefulness, trust, visibility of the product, and demonstrability. Together, these factors resulted in the customers’ successful transition from the pre-purchase stage to the purchase decision stage.